Determination of Osmotically Inactive Volume of Murine Enterocytes - Ogurtsova, Viktoriya V.; Kovalenko, Svetlana Ye.; Kovalenko, Igor F.; Gordiyenko, Olga I. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(1):93-97.